Beyond antibiotics: CRISPR/Cas9 triumph over biofilm-associated antibiotic resistance infections - Zuberi, Azna; Ahmad, Nayeem; Ahmad, Hafiz; Saeed, Mohd; Ahmad, Irfan (Frontiers in Cellular and Infection Microbiology, 2024)
A complex structure known as a biofilm is formed when a variety of bacterial colonies or a single type of cell in a group sticks to a surface. The extracellular polymeric compounds that encase these cells, often consisting of proteins, eDNA, and polysaccharides, exhibit strong antibiotic resistance. Concerns about biofilm in the pharmaceutical industry, public health, and medical fields have sparked a lot of interest, as antibiotic resistance is a unique capacity exhibited by these biofilm-producing bacteria, which increases morbidity and death. Biofilm formation is a complicated process that is controlled by several variables. Insights into the processes to target for the therapy have been gained from multiple attempts to dissect the biofilm formation process. Targeting pathogens within a biofilm is profitable because the bacterial pathogens become considerably more resistant to drugs in the biofilm state. Although biofilm-mediated infections can be lessened using the currently available medications, there has been a lot of focus on the development of new approaches, such as bioinformatics tools, for both treating and preventing the production of biofilms. Technologies such as transcriptomics, metabolomics, nanotherapeutics and proteomics are also used to develop novel anti-biofilm agents. These techniques help to identify small compounds that can be used to inhibit important biofilm regulators. The field of appropriate control strategies to avoid biofilm formation is expanding quickly because of this spurred study. As a result, the current article addresses our current knowledge of how biofilms form, the mechanisms by which bacteria in biofilms resist antibiotics, and cutting-edge treatment approaches for infections caused by biofilms. Furthermore, we have showcased current ongoing research utilizing the CRISPR/Cas9 gene editing system to combat bacterial biofilm infections, particularly those brought on by lethal drug-resistant pathogens, concluded the article with a novel hypothesis and aspirations, and acknowledged certain limitations.